Collapse, war and reconstruction in Uganda : an analytical narrative on state-making - Golooba-Mutebi, Frederick (2008)
Since independence from British colonial rule, Uganda has had a turbulent political history characterised by putsches, dictatorship, contested electoral outcomes, civil wars and a military invasion. There were eight changes of government within a period of twenty-four years (from 1962-1986), five of which were violent and unconstitutional. This paper identifies factors that account for these recurrent episodes of political violence and state collapse. While colonialism bequeathed the country a negative legacy including a weak state apparatus, ethnic division, skewed development, elite polarisation and a narrow economic base, post-colonial leaders have on the whole exacerbated rather than reversed these trends. Factors such as ethnic rivalry, political exclusion, militarisation of politics, weak state institutions, and unequal access to opportunities for self-advancement help to account for the recurrent cycles of violence and state failure prior to 1986. External factors have also been important, particularly the country’s politically turbulent neighbourhood, the outcome of political instability and civil conflict in surrounding countries. Neighbourhood turbulence stemming from such factors as civil wars in Congo and Sudan has had spill-over effects in that it has allowed insurgent groups geographical space within which to operate as well as provided opportunities for the acquisition of instruments of war with which to destabilise the country. Critical to these processes have been the porosity of post-colonial borders and the inability by the Ugandan state to exercise effective control over its entire territory. By demonstrating the interplay between internal and external factors in shaping Uganda’s postcolonial experience, the paper makes an important shift away from conventional explanations that have focused disproportionately on internal processes. Lastly, the paper provides pointers to areas of further research such as the economic foundations of conflict that should ultimately strengthen our understanding of factors that combine to make state-making fail or succeed.